2017
DOI: 10.3892/mmr.2017.7156
|View full text |Cite
|
Sign up to set email alerts
|

c-Maf inducing protein inhibits cofilin-1 activity and alters podocyte cytoskeleton organization

Abstract: The glomerular visceral epithelial cells, also termed podocytes, are key in maintaining the normal renal filtration barrier. Although it has been demonstrated that stimulation of c‑Maf inducing protein (CMIP) expression is involved in podocyte damage, the molecular events during this process remain unclear. In the current study, CMIP‑induced proximal signaling was investigated by focusing on its effect on cofilin‑1 activity in puromycin aminonucleoside (PA)‑damaged podocytes. An obvious elevation of CMIP expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These results, along with other data obtained from the transgenic mouse model, suggest a defect in T cell activation associated with CMIP expression. Based on these findings, we further analyzed the expression of Cofilin-1, a major actor in the dynamic rearrangement of the actin cytoskeleton 23 whose activity was recently reported to be negatively regulated by CMIP in podocytes, 24 by Western blotting. We found that phosphorylated Cofilin-1, the inactive form of Cofilin-1, was dramatically increased in transgenic T cells at 60 min after stimulation compared to its levels in WT T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results, along with other data obtained from the transgenic mouse model, suggest a defect in T cell activation associated with CMIP expression. Based on these findings, we further analyzed the expression of Cofilin-1, a major actor in the dynamic rearrangement of the actin cytoskeleton 23 whose activity was recently reported to be negatively regulated by CMIP in podocytes, 24 by Western blotting. We found that phosphorylated Cofilin-1, the inactive form of Cofilin-1, was dramatically increased in transgenic T cells at 60 min after stimulation compared to its levels in WT T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, silencing c-mip prevented IL-17 related podocyte apoptosis by promoting persistent activation of NF-κB and upregulation of anti-apoptotic protein Bcl-2 (137). C-mip is a protein whose expression is suppressed in healthy glomeruli (138) and increased in pathological conditions and has been associated with cytoskeletal disorganization in podocytes and proteinuria (139,140).…”
Section: Podocytesmentioning
confidence: 99%
“…Cofilin is essential for maintaining normal podocyte structure and facilitating structural changes in actin during podocyte injury and recovery. Cofilin knockout mice develop persistent proteinuria by 3 months of age and exhibit more severe proteinuria along with foot protrusions by 18 months of age [ 66 ]. The RhoA/ROCK/LIMK1 pathway can mediate cofilin phosphorylation, altering the ratio of phosphorylated to nonphosphorylated cofilin and disrupting actin dynamics, ultimately leading to cytoskeletal damage [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%